Interpersonal emotion regulation and symptom dimensions of psychosis proneness in young adults - Riehle, Marcel; Allmandinger, Hannah; Prüßner, Luise (Schizophrenia, 2024)
This study investigated the relative associations of psychosis proneness symptom domains with habitual interpersonal emotion regulation (IER) use in a sample of young adults (n = 420, age 18-29). Multiple regression models showed that attenuated negative symptoms were related to using less, while attenuated positive symptoms and depression were related to using more IER. These findings suggest symptom-specific IER patterns across different symptom dimensions of psychosis proneness.